Layanan Bimbingan Kelompok Teknik Socrates dalam Mengembangkan Perencanaan Karir Siswa Kelas XI SMA Negeri 2 Pemalang - M. Andika Arsya R; Arri Handayani; G. Rohastono Ajie (Journal on Education, 2023)
The main problem studied is the Socrates Technical Group Guidance Service in Improving Career Planning for Class XI Students of SMA Negeri 2 Pemalang. The research method used is true experimental with pretest-posttest control group design. The population in this study were all students of class XI SMA Negeri 2 Pemalang, totaling 144 students consisting of 5 classes. The sampling technique used is cluster random sampling technique. The analysis used to test the validity is the product moment and reliability using the alpha formula. The final conclusion from the results of the t-test analysis that the posttest between the experimental group and the control group obtained tcount = 10.3. To ascertain whether the difference is significant, the results are consulted with ttable. With db = (n1+n2)-2 = (10+10)-2=18 and a significant level of 5%, ttable = 2.021 is obtained. Because tcount = 10.3 ˃ ttable = 2.021, tcount is greater than ttable, meaning that Ho is rejected and Ha is accepted, so it can be concluded that "There is an effect of group guidance services using the social technique on career planning in class XI at SMA Negeri 2 Pemalang" at the level significant 5%. Suggestions that researchers can convey should supervising teachers at schools provide advanced services with regard to career planning.